Forgetfulness, postures and impostures in the transition in the early works of Rafael Chirbes (XXI Century. Spanish Literature and Culture, 2015)
The first novels of Rafael Chirbes, En la lucha final (1991) y La buena letra (1992) have so far deserved little attention from critics. However, in those early texts, Chirbes offers a critical view of the Transition from the intra-histories of two completely different universes, one around the world of culture, another in a humble Valencian people. Its protagonists act as bulwarks to show that falsehood, imposture, forgetfulness, folds and lies became keys and ways of being in social change.
Keywords: Rafael Chirbes; woman; history; novel; oblivion; falsehood